(untitled) (Philological Studies, 2019)
Peculiarities of Komi-Permyak proverbs borrowed from the Russian language are described in the article. Subjects groups of mastered proverbs are presented, ways of their occurrence in the Komi-Permyak language are described. Attempt to distinguish signs of proverbs-loanwords was made (the presence of Russisms components, the use of figurative correlations typical for Russian, grammaticalness according to Russian structural schemes). Proverbs figurativeness modification, accompanying the process of its mastering, and semantic changes in the statement are marked. Conclusion, concerning the ability of adopted proverbs to acquire its colouring in borrowing culture, is made.